Restorative Yet Incomplete: The Dilemma of Progressive Legal Reform in Indonesia - Sihole, Michael Deo Leorenzius (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Restorative justice represents an alternative approach in the criminal justice system that prioritizes the restoration of relationships among offenders, victims, and the community. In Indonesia, its implementation remains limited and has yet to be fully integrated into the broader justice framework. This study aims to examine the application of restorative justice principles across various levels of law enforcement, identify normative, institutional, and sociological barriers, and propose strategic recommendations for national legal reform. Employing a juridical-normative and empirical methodology—through document analysis and semi-structured interviews—this research reveals that the application of restorative justice remains fragmented. Contributing factors include an underdeveloped legal foundation, inadequate institutional capacity, and cultural resistance within communities. The study concludes that comprehensive national regulations are essential to institutionalize restorative justice principles, thereby fostering a more humane, participatory, and restorative criminal justice system that moves beyond retributive paradigms.